Implikasi Body Shaming Terhadap Kesehatan Mental Remaja: Analisis Tafsir Al-Azhar Q.S. Al-Hujurat Ayat 11 dan 12 - Dara Dilla Az-zahra; Sukiman (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the implications of body shaming on adolescent mental health through the Al-Azhar interpretation of Q.S. Al-Hujurat verses 11 and 12. Advances in technology and social media have transformed human interactions, but have also triggered social problems such as body shaming, which is the act of criticizing or making negative comments about someone's body shape or size, as well as self-deprecating regarding physical appearance. This phenomenon is widespread on digital platforms, with a high prevalence among adolescents who often hear jokes about other people's bodies. The impact of body shaming is very significant on mental health, causing disorders such as decreased self-confidence, anxiety, depression, eating disorders, social isolation, and psychological trauma. In Islam, the values of the Qur'an provide guidelines for social interaction. Q.S. Al-Hujurat verse 11 expressly prohibits acts of belittling, criticizing, and giving bad names. Al-Azhar's interpretation by Buya Hamka explains that making fun of and belittling is a reflection of arrogance and forgetting one's own shortcomings. This verse also prohibits bad, demeaning nicknames. Meanwhile, Q.S. Al-Hujurat verse 12 prohibits prejudice, faultfinding, and gossiping. Prejudice often leads to body shaming, with physical faultfinding aimed at humiliating, and backbiting about appearance being compared to eating one's own dead brother. This literature review used the tahlili method to analyze verses 11 and 12 of Q.S. Al-Hujurat, along with the Al-Azhar commentary as primary sources. The results indicate that body shaming violates the fundamental principles of humanity and brotherhood in Islam, with detrimental impacts on adolescent mental health, including low self-esteem, anxiety, depression, paranoia, and isolation. Therefore, implementing Qur'anic values through moral education, increasing self-awareness, using appropriate terms, preventing prejudice, and developing a positive environment is essential in preventing and addressing body shaming among the younger generation. Keywords: Body Shaming; Adolescent Mental Health; Al-Azhar commentary; Q.S. Al-Hujurat verse 11; Q.S. Al-Hujurat Verse 12